An Evolutionary Perspective of Dyslexia, Stress, and Brain Network Homeostasis - Kershner, John R. (Frontiers in Human Neuroscience, 2021)
Evolution fuels individual variability in neuroplasticity, reflected in brain anatomy and functional connectivity of the expanding neocortical regions subserving reading ability. Such variability is orchestrated by an evolutionarily-conserved, balance between stress-induced and cognitive-growth gene expression programs. An evolutionary developmental model of dyslexia, suggests that prenatal and childhood subclinical stress becomes a risk factor for dyslexia when physiological adaptations to stress promoting long-term fitness, may attenuate neuroplasticity in the brain regions recruited for reading. Stress has the potential to blunt the cognitive-growth functions of the predominantly right hemisphere Ventral and Dorsal attention networks, which are primed with high levels of synaptic plasticity, and are critical for acquiring reading skills. The attentional networks, in collaboration with the stress-responsive Default Mode network, modulate entrainment of the low frequency auditory oscillations in speech linked etiologically to dyslexia. Thus, dyslexia may result from positive, but costly adaptations to stress system dysregulation: protective measures that upset the stress/growth balance of processing to favor the Default Mode network, compromising development of the attentional networks. Such a normal-variability conceptualization of dyslexia is at odds with the widely-held assumption that dyslexia results from a neurological abnormality. To put the current model in the broader perspective of the state of the field, a more traditional evolutionary model of dyslexia is pesented for comparison.